Entre la vida y la muerte - Pulido Varon, Heidi Smith (2024)
Caucasia, municipality of Bajo Cauca Antioqueño in Colombia, expresses necropolitical and necrocapitalist dynamics that State and illegal actors deploy on the territory and specifically on the Cauca River. This action permeates the daily life and subjectivity of local communities in affective, territorial, identity and memory aspects, which are built in experiences and life trajectories in the territory. This text analyzes from a qualitative approach and social phenomenological method, which, from the experience of six participants, captures some meanings of this tributary. The field work considered interviews and accompaniment to their work in situ. Among the results, local meanings are highlighted, which emerge in the felt experience linked to the river, coexisting and in tension with hegemonic positions of the State and the armed groups.